1997
DOI: 10.1046/j.1469-7580.1997.19130451.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and morphology of accessory heads of flexor pollicis longus and flexor digitorum profundus (Gantzer's muscles)

Abstract: In 1813 Gantzer described 2 accessory muscles in the human forearm which bear his name (Wood, 1868; Macalister, 1875; Testut, 1884; Le Double, 1897). The more frequent of the 2 accessory muscles or ‘accessorius ad pollicem’ was found to arise from the coronoid process of the ulna, coursing distally to attach into the flexor pollicis longus muscle (flexor pollicis longus accessory head, FPLah). The less frequently observed or ‘accessorius ad flexorem profundum digitorum’ was again found to arise from the corono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
99
2
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(128 citation statements)
references
References 0 publications
19
99
2
8
Order By: Relevance
“…The deep layer further develops into FDP, FPL, and pronator quadratus muscle, but incomplete differentiation creates the AHFPL (Hollinshead, 1964;Jones & Abrahams). The occurrence of an accessory head of FDP in Mangini; Jones & Abrahams, 1997; and our report, all seem to attest to this hypothesis.…”
Section: Discussionsupporting
confidence: 68%
“…The deep layer further develops into FDP, FPL, and pronator quadratus muscle, but incomplete differentiation creates the AHFPL (Hollinshead, 1964;Jones & Abrahams). The occurrence of an accessory head of FDP in Mangini; Jones & Abrahams, 1997; and our report, all seem to attest to this hypothesis.…”
Section: Discussionsupporting
confidence: 68%
“…Most of the times such muscular variations are Muscular variations are commonly observed during cadaveric dissection. These variations are in the form of abnormal origin or insertion, accessory slips of the muscles, anatomical [3,4,5]. In the present study it is 36%, little higher on left side 38% than right side 34%, this is accordance with the results by Le Double.…”
Section: Introductionsupporting
confidence: 82%
“…The most common singular point of origin from under the surface of FDS has been reported by M. Jones [4]. Wood has reported the origin of ahFPL from coronoid process of ulna.…”
Section: Methodsmentioning
confidence: 94%
“…Although there are reports that a prevalence of aFPL When present the GM mostly originated from the medial epicondyle of the humerus or the under surface of FDS muscle, as in the present case [8]. It has been reported that the insertion sites of the GM were the FDP or the FPL, and the more common form of the GM was aFPL [2,[8][9][10].…”
Section: Discussionmentioning
confidence: 78%